Method to interactively visualize and navigate related information. (30th November 2018) - Hernando, A.; Bobadilla, J.; Ortega, F.; Gutiérrez, A.
Highlights: Innovative visualization of tree graphs. Brand new navigation method for tree based information. Method formalization. Smooth transitions through the navigation of information. Abstract: In this paper, a formal method is presented to: (1) establish a system to visualize huge quantities of related information (2) graphically show the degree of similarity between these related documents (3) navigate between related documents so that the views are reconfigured in a dynamic and gradual way. This method uses, as input, a set of documents that have been related using any existing algorithm (relationships based on contents, on votes to contents, on social relations, on demographic information, etc.). The proposed method includes two different visualization and navigational versions related to: (a) visualization by explicit graph and (b) visualization by implicit graph. As a summary, the following characteristics are presented: (1) this method maximizes the information that is displayed at each moment, so that a balance is found between: (a) the number of relations shown, (b) the number of documents viewed, (c) the amount of information presented by each document and (d) how to show the degree of similarity between documents, (2) the method includes specific rules of interaction with the user to allow navigation in a simple, gradual and intuitive way. Graphic abstract: